Book Reviews (The Australian journal of anthropology, 1973)
The Ieland of Menatruating Men: Religion in Wogeo, New Guinea. By Ian Hogbin Anthropology in Oceania: Essays presented to Ian Hogbin. Edited by L. R. Hiatt and C. Jaywardena Habu: The Innovation of Meaning in Daribi Religion. By Roy Wagner The Chimbu: A Study of Change in the New Guinea Highlands. By Paula Brown Physical Anthropology of the Eastern Highlands of New Guinea. By R. A. Littlewood Change and Development in Rural Melanesia. Edited by Marion Ward A Study in Structural Semantics: The Siriono Kinship System. By Harold W. Scheffler and Floyd G. Lounsbury Three Styles in the Study of Kinship. By J. A. Barnes Socialization: The Approach from Social Anthropology. Edited by Philip Mayer Primitive Law, Past and Present. By A. S. Diamond The Translation of Culture: Essays to E. E. Evans-Pritchard. Edited by T. O. Beidelman Essays on the Caste Syetem. By Celestin Bouglé Religious Experience: its nature and function in the human psyche. By Walter Houston Clark Man for Humanity. On Concordance vs Discord in Human Behavior. Edited by H Masserman and J. J. Schwab. Charles C. Thomas The Emergence of Man. By John E. Pfeiffer Papers in Economic Prehistory: Studies by Members and Associates of the British Academy Major Research Project in the Early History of Agriculture. Edited by E. S. Higgs Yirawala, Artist and Man. By Sandra le Brun Holmes Science and Archaeology. Edited by Robert H. Brill Tongues of Men and Angela. By William J. Samarin. Macmillan Biology: A Search for Order in Complexity. By J. N. Moore and H. S. Slusher Moko: or Maori Tattooing. By H. G. Robley. Chapman and Hall Frozen Tombs: the Pazyryk Burials of Iron-Age Horsemen. By Sergei I. Rudenko Anthropology for our Times. By Lois Brauer Cover